Effects of organic and mineral fertilizer inputs on maize yield and soil chemical properties in a maize cropping systems in Meru South District, Kenya - Mucheru-Muna, M.; Mugendi, DN; Kung'u, J.B.; Mugwe, J; Bationo, B. André (Springer, 2007)
Soil nutrient depletion as a result of continuous cultivation of soils without adequate addition of external inputs is a major challenge in the highlands of Kenya. An experiment was set up in Meru South District, Kenya in 2000 to investigate the effects of different soil-incorporated organic (manure, Tithonia diversifolia, Calliandra calothyrsus, Leucaena leucocephala) and mineral fertilizer inputs on maize yield, and soil chemical properties over seven seasons. On average, tithonia treatments (with or without half recommended rate of mineral fertilizer) gave the highest grain yield (5.5 and 5.4 Mg ha?1 respectively) while the control treatment gave the lowest yield (1.5 Mg ha?1). After 2 years of trial implementation, total soil carbon and nitrogen contents were improved with the application of organic residues, and manure in particular improved soil calcium content. Results of the economic analysis indicated that on average across the seven seasons, tithonia with half recommended rate of mineral fertilizer treatment recorded the highest net benefit (USD 787 ha?1) while the control recorded the lowest (USD 272 ha?1). However, returns to labor or benefit-cost ratios were in most cases not significantly improved when organic materials were used.